A europium-based metal-organic framework for fluorescent detection of uric acid and its preparation method and application
Through the synthesis of Eu-MOF, the problem of quenching of fluorescent sensing materials in uric acid detection is solved, and MOF materials with high proton conductivity and water stability are realized, with fast response and high sensitivity uric acid detection capabilities.
Patent Information
- Application Number
- CN202410778489.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-17
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-06-17
AI Technical Summary
The prior art has the problem of quenching of fluorescent sensing materials in uric acid detection, and the manufacturing of MOF materials with high proton conductivity and water stability is still a major challenge.
Using the europium-based metal-organic framework Eu-MOF, synthesized by H4TTDI and Eu(NO3)3·6H2O under hydrothermal conditions, a material with excellent water stability and high porosity was obtained, and its performance was optimized by the steps of sonication and lactic acid addition.
Eu-MOF exhibits blue shift and enhanced fluorescence sensing to uric acid, has fast response and high sensitivity, a detection limit of 0.062 μM, and shows good proton conductivity at 45°C and 98% relative humidity.
Smart Images

Figure CN118725322B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of multifunctional bioassay materials, and in particular relates to a europium-based metal-organic framework for fluorescent detection of uric acid, and a preparation method and application thereof. Background Art
[0002] Metal-organic frameworks (MOFs) are a new type of functional material constructed through coordination bonds between organic ligands and metal ion / metal cluster nodes. In recent years, they have been widely used in storage / separation, magnetism, fluorescence sensing, catalysis, proton conductivity, etc. due to their high porosity and tunable pore properties. Uric acid (UA), also known as 2,6,8-trihydroxypurine, is a purine metabolite that is commonly found in biological fluids, including urine and blood. UA concentrations in blood are associated with hyperuricemia, gout, arthritis, kidney disease, and other diseases. Therefore, simple and accurate detection of UA in urine or blood may help in the diagnosis of many diseases.
[0003] At present, UA detection methods include electrochemical methods, enzymatic methods, chromatography, Raman spectroscopy, and luminescence spectroscopy. Electrochemical and enzyme sensing are traditional UA detection methods. The oxidation peak potentials of UA and ascorbic acid (AA) are almost the same, which leads to the overlap of the oxidation peak potentials of UA and AA, making the distinction between UA and AA complicated. Enzymatic detection of UA usually requires the use of expensive enzyme reagents and the adjustment of the pH value in the culture medium, making the detection process complicated. Fluorescence spectrophotometry has been rapidly developed due to its advantages such as rapidity, accuracy, and high sensitivity. For example, the MOF called Hf-UiO-66-Py can detect UA with a detection limit of 1.4μM, while the Eu-TDA luminescent probe provides a rapid and highly sensitive response to UA with a detection limit of 0.689μM. However, these MOF test materials usually exhibit quenched fluorescence when sensing UA, without obvious fluorescence enhancement or color change.
[0004] In addition, MOFs are known as efficient proton conductors due to their porous structure and extensive hydrogen bonding network. Compared with traditional solid-state plasma conducting materials, MOFs offer a more direct approach to design and tune their structure and properties. However, fabricating water-stable MOFs with high proton conductivity remains a major challenge.
[0005] Therefore, how to provide a MOF material that has both excellent photoelectric properties and water stability is a technical problem that technicians in this field urgently need to solve. Summary of the invention
[0006] In order to solve the above technical problems, the present invention proposes a europium-based metal-organic framework for fluorescent detection of uric acid, and a preparation method and application thereof.
[0007] To achieve the above object, the present invention provides the following technical solutions:
[0008] A europium-based metal-organic framework for fluorescent detection of uric acid, the molecular formula is:
[0009] {[(CH3)2NH2]2[Eu(TTDI)H2O]2·2H2O·7DMF} n .
[0010] The n value is not limited because the degree of polymerization of the europium-based metal-organic framework in the present invention is determined by the specific preparation process and is uncertain. The europium-based metal-organic framework obtained in the present invention is a mixture, in which the n value can be any value, and its specific numerical range has no effect on the product properties.
[0011] A method for preparing a europium-based metal-organic framework for fluorescent detection of uric acid comprises the following steps:
[0012] H4TTDI and Eu(NO3)3·6H2O are mixed and added to a binary solution, and then lactic acid is added after ultrasonic treatment, and the mixture is stored under hydrothermal conditions. Finally, after post-treatment, the europium-based metal-organic framework is obtained, which is recorded as Eu-MOF.
[0013] Beneficial effects: The H4TTDI used in the present invention is specifically a ligand 5,5'-(thiophene[3,2-b]-2,5-diphenyl)terephthalic acid, which has a rigid electron-rich main chain and a dithiophene part, giving it excellent photoelectric properties. The Eu-MOF synthesized using this ligand has excellent water stability, as well as significant porosity and a wide range of hydrogen bond networks. The raw materials are selected through screening, making full use of their advantages, and exerting their important application potential in the field of biological and chemical molecular detection.
[0014] The Eu-MOF obtained by the present invention exhibits blue shift and enhanced fluorescence sensing of uric acid (UA), has rapid response and high sensitivity, and the detection limit is 0.062μM. At the same time, the present invention studies the proton conductivity of Eu-MOF and finds that at 45°C and 98% relative humidity, the maximum value of proton conductivity is 4.82×10 -3 S cm -1 Compared with traditional solid-state plasma conductive materials, MOFs in the present invention provide a more direct design and tuning method in terms of structure and performance. It can be seen that the Eu-MOF synthesized using this ligand has excellent water stability, as well as significant porosity and an extensive hydrogen bond network.
[0015] Preferably, the binary solution is a mixed solution of DMF and water, wherein the volume ratio of DMF to water is 5:2.
[0016] Preferably, the ultrasonic treatment time is 30 min and the ultrasonic power is 360 W.
[0017] Preferably, the temperature of the hydrothermal condition is 140° C. and the storage time is 3 days.
[0018] Preferably, the ratio of the added amounts of H4TTDI, Eu(NO3)3·6H2O, binary solution and lactic acid is 0.05mmol:0.08mmol:7mL:0.2mL.
[0019] Preferably, the post-treatment includes cooling, filtering, washing and air-drying.
[0020] Application of a europium-based metal-organic framework for fluorescent detection of uric acid in uric acid fluorescence sensing.
[0021] Uric acid is commonly found in biological fluids, including urine and blood. UA concentrations in the blood are associated with hyperuricemia, gout, arthritis, kidney disease and other diseases. Therefore, simple and accurate detection of UA in urine or blood may help diagnose many diseases. Electrochemical and enzyme sensing are traditional methods for UA detection. The oxidation peak potentials of UA and ascorbic acid (AA) are almost the same, which leads to the overlap of the oxidation peak potentials of UA and AA, making the distinction between UA and AA complicated. Enzymatic detection of UA usually requires the use of expensive enzyme reagents and the need to adjust the pH value in the culture medium, making the detection process complicated. The europium-based metal-organic framework (Eu-MOF) material obtained in the present invention showed blue shift and enhanced fluorescence sensing of UA for the first time, with rapid response and high sensitivity, and can be well applied to uric acid fluorescence sensing.
[0022] Compared with the prior art, the present invention has the following advantages and technical effects:
[0023] The europium-based metal-organic framework Eu-MOF provided by the present invention can quickly detect uric acid (UA) with high selectivity and sensitivity, and the detection limit is 0.062μM. Eu-MOF represents the first Ln-MOF for fluorescence blue shift enhanced detection of UA. In addition, due to its excellent water stability and rich hydrogen bond network, Eu-MOF also exhibits good proton conductivity, with a maximum conductivity value of 3.34×10 at 50°C under 98% relative humidity. -3 S cm -1 , for Eu-MOF, its excellent fluorescence sensing ability and proton conductivity mean that it is a potentially important multifunctional bioassay material. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:
[0025] Figure 1 The structure diagram of Eu-MOF synthesized in Example 1;
[0026] Among them, (a) is Eu in Eu-MOF III (b) Coordination environment diagram of Eu in Eu-MOF III (c) is the two-dimensional structure view of Eu-MOF; (d) is the three-dimensional structure view of Eu-MOF;
[0027] Figure 2 The infrared spectra of Eu-MOF and H4TTDI obtained in Example 1;
[0028] Figure 3 is the X-ray powder diffraction pattern of Eu-MOF obtained in Example 1;
[0029] Figure 4 PXRD spectra of the solvent stability (a) and pH stability (b) of the Eu-MOF obtained in Example 1;
[0030] Figure 5 TG spectrum of Eu-MOF obtained in Example 1;
[0031] Figure 6 Solid-state emission diagram of Eu-MOF and H4TTDI obtained in Example 1 (a); CIE diagram of Eu-MOF and H4TTDI (b); Fluorescence emission diagram of Eu-MOF in different solvents (c); Fluorescence lifetime diagram of Eu-MOF and H4TTDI (d);
[0032] Figure 7 The solid-state UV singlet energy level calculations and DFT theoretical calculations for H4TTDI, UA, and the energy transfer diagram; (a) is the UA energy level; (b) is the H4TTDI energy level; (c) is the solid-state UV singlet energy calculation diagram in the energy transfer diagram; (d) is the DFT density functional theory calculation diagram;
[0033] Figure 8 The fluorescence emission spectra of the Eu-MOF suspension obtained in Example 1 for different biomarkers (a), the UA spectrum of Eu-MOF fluorescence titration (the inset is for naked eye identification) (b), the detection limit of UA (c) and the schematic diagram of the anti-interference characteristics of substances in simulated urine (d);
[0034] Fig. 9The visual effect picture of the Eu-MOF obtained in Example 1 after being in contact with UA (a), the actual photo of the flexibility of the film (b), the visual effect picture of the LED lamp bead detection (c), and the visual effect picture of the test paper for detecting simulated urine (d);
[0035] Fig.10 The proton conduction channel diagram (a), hydrogen bond network diagram (b), proton conductivity under different humidity conditions at 25°C (c), and proton conductivity under different temperature conditions at 98% RH (d) of the Eu-MOF obtained in Example 1, wherein the inset is the Arrhenius coupling diagram;
[0036] Fig.11 Eu-MOF for characterization. DETAILED DESCRIPTION
[0037] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0038] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.
[0039] The embodiment of the present invention discloses a europium-based metal-organic framework for fluorescent detection of uric acid, the molecular formula of which is:
[0040] {[(CH3)2NH2]2[Eu(TTDI)H2O]2·2H2O·7DMF} n .
[0041] The n value is not limited because the degree of polymerization of the europium-based metal-organic framework in the present invention is determined by the specific preparation process and is uncertain. The europium-based metal-organic framework obtained in the present invention is a mixture, in which the n value can be any value, and its specific numerical range has no effect on the product properties.
[0042] The embodiment of the present invention also discloses a method for preparing a europium-based metal-organic framework for fluorescent detection of uric acid, comprising the following steps: mixing H4TTDI and Eu(NO3)3·6H2O and adding a binary solution, adding lactic acid after ultrasonic treatment, and storing under hydrothermal conditions, and finally post-treating to obtain the europium-based metal-organic framework, recorded as Eu-MOF.
[0043] In a preferred embodiment, the binary solution is a mixed solution of DMF and water, wherein the volume ratio of DMF to water is 5:2.
[0044] In a preferred embodiment, the ultrasonic treatment time is 30 minutes and the ultrasonic power is 360W.
[0045] In a preferred embodiment, the temperature of the hydrothermal condition is 140° C. and the storage time is 3 days.
[0046] In a preferred embodiment, the ratio of the added amounts of H4TTDI, Eu(NO3)3·6H2O, binary solution and lactic acid is 0.05mmol:0.08mmol:7mL:0.2mL.
[0047] In a preferred embodiment, the post-treatment includes cooling, filtering, washing and air-drying.
[0048] The embodiment of the present invention also discloses an application of a europium-based metal-organic framework for fluorescent detection of uric acid in uric acid fluorescence sensing.
[0049] Unless otherwise specified, the raw materials in the examples of the present invention were purchased from commercial sources;
[0050] The room temperature or normal temperature in the embodiments of the present invention refers to 25±3°C.
[0051] Example 1
[0052] A method for preparing a europium-based metal-organic framework for fluorescent detection of uric acid comprises the following steps:
[0053] 0.0279 g H4TTDI (0.05 mmol) and 0.0356 g Eu(NO3)3·6H2O (0.08 mmol) were added to a 25 mL Teflon cup, and 7 mL of binary solution (V DMF :V H2O =5:2), then ultrasonically treated for 30 min at an ultrasonic power of 360 W, 200 μL of lactic acid was added, and stored at 140 ° C for 3 d. After the reaction, the resulting mixture was cooled to room temperature and filtered to obtain yellow block crystals, which were air-dried to obtain europium-based metal-organic framework Eu-MOF, with a yield of 48.3%.
[0054] TGA and elemental analysis results: Based on H4TTDI.IR (KBr, cm -1):3614(w),3437(w),3326(w),3205(w),3063(w),2922(w),1674(s),1567(s),1441(s),14 06(s),1255(m),1037(s),916(m),835(s),760(s),734(s),648(m),522(m),446(w).Calcd for C 67 H 54 Eu2N2O 24 (%): C, 36.174; H, 3.621; N, 4.809; S, 5.901. Found (%): C, 33.216; H, 3.191; N, 2.861; S, 5.861.
[0055] The final chemical composition was determined to be Eu(NO3)3·6H2O.
[0056] Comparative Example 1
[0057] The only difference from Example 1 is that Eu(NO3)3·6H2O is replaced by an equal amount of Er(NO3)3·6H2O. The other process parameters and steps are the same as those in Example 1.
[0058] Comparative Example 2
[0059] The only difference from Example 1 is that H4TTDI is replaced by an equal amount of ligand H4ADIP (azadiisophthalic acid). Other process parameters and steps are the same as those in Example 1.
[0060] Comparative Example 3
[0061] The only difference from Example 1 is that the binary solution is replaced by a solution of equal amounts of DEF and water mixed in a volume ratio of 1:1. Other process parameters and steps are the same as those in Example 1.
[0062] Comparative Example 4
[0063] The only difference from Example 1 is that lactic acid is replaced by an equal amount of formic acid. Other process parameters and steps are the same as those in Example 1.
[0064] Comparative Example 5
[0065] The only difference from Example 1 is that the ratio of the added amounts of H4TTDI, Eu(NO3)3·6H2O, binary solution and lactic acid is 0.05mmol:0.065mmol:8mL:0.4mL. The other process parameters and steps are the same as those in Example 1.
[0066] Comparative Example 6
[0067] The compound was prepared using the method in the prior art (Shuting Xu, Jiandong Pang, Bo Zhang, Yunwu Li, YanYang, and Jun Li. Crystal Growth & Design. 2024, 24(3), 1410-1420. DOI: 10.1021 / acs.cgd.3c01372.), which was different from Example 1 only in that the ligand H4TTDI was replaced by 5′-methyl-[1,1′:3′,1″-triphenyl]-3,3″,5,5″-tetracarboxylic acid (H4mtptc), DMF was replaced by DMA, and the temperature was changed to 160°C to obtain the target crystal with the chemical formula [Me2NH2]2[Eu3(mtptc)2(CH3COO)3]·DMA·H2O.
[0068] The obtained compound was used for UA fluorescence detection. The results showed that with the addition of UA, the concentration was continuously quenched, and the detection limit was 2.06μM.
[0069] Comparative Example 7
[0070] The compound was prepared by the method in the prior art (Li-Juan Han, Ya-Jie Kong, Guo-Zheng Hou, Hua-Chong Chen, Xing-Min Zhang, and He-Gen Zheng. Inorganic Chemistry. 2020, 59(10), 7181-7187. DOI: 10.1021 / acs.inorgchem.0c00620.), and the synthesis method comprises the following steps:
[0071] 2,5-thiophenedicarboxylic acid (0.12mmol, 0.020g), Eu(NO3)3·6H2O (0.06mmol, 0.027g) and glacial acetic acid (60μL) in distilled water (3mL) were sealed in a polytetrafluoroethylene container and heated at 180℃ for 96h. After cooling to room temperature, blocky yellow crystals appeared. The crystal chemical formula is [Eu2(TDA)4(OOCCH)2H2O2].
[0072] The obtained compounds were used for UA fluorescence detection, and the results showed that the fluorescence test λ ex is 302nm. With the increase of uric acid (5×10 -3 mol·L -1 , Na3PO4 solution), the concentration was continuously quenched, and the detection limit was 0.0689μM.
[0073] Comparative Example 8
[0074] The compound was prepared by the method in the prior art (Li-Juan Han, Ya-Jie Kong, Xing-Min Zhang, Guo-Zheng Hou, Hua-Chong Chena and He-Gen Zheng. Journal of Materials Chemistry C. 2021, 9, 6051-6061. DOI: https: / / doi.org / 10.1039 / D1TC01204E), which was different from Example 1 only in that the ligand was changed to terephthalic acid, the temperature was changed to 180°C, and the solvent was changed to 60 μL of glacial acetic acid. The crystal chemical formula is [Eu2(PDA)3(H2O)3].
[0075] The obtained compound was used for UA fluorescence detection, and the results showed that with the increase of uric acid (1.14×10 4 M -1 ) was added, the concentration was continuously quenched, and the detection limit was 0.601 μM.
[0076] Comparative Example 9
[0077] The compound was prepared using the method in the prior art (Shano M. Pirot, Khalid M. Omer, Azad H. Alshatteri, Gona K. Ali, Omer BAShatery. Spectrochimica Acta Part A: Molecular and Biomolecular Spectroscopy. 2023, 291, 1386-1425. DOI: https: / / doi.org / 10.1016 / j.saa.2023.122340), the only difference from Example 1 being that Eu(NO3)3·6H2O in the synthesis method was replaced by Cr(NO3)3·9H2O. The coordination was changed to 0.72 g (0.1 M) aminoterephthalic acid and 0.4 g (0.3 M) sodium hydroxide dispersed in 30 mL deionized water, and then ultrasonically treated for 30 minutes. The resulting solution was heated in a polytetrafluoroethylene-lined autoclave at 150 ° C for 12 hours. After the reaction was completed, the reaction mixture was cooled to room temperature, the green solid was collected, and washed with deionized water and methanol. The product was then dried in an oven at 80 ° C to obtain the target compound.
[0078] The obtained compound was used for UA fluorescence detection, and the results showed that with the addition of uric acid (25.0 μM-425.0 μM), the concentration was continuously quenched, and the detection limit was 1.10 μM.
[0079] Technical effects:
[0080] The performance characterization and technical effects such as fluorescence effect of Eu-MOF obtained in Example 1 were tested.
[0081] 1. Performance characterization:
[0082] 1-1.X-ray crystal structure:
[0083] X-ray crystal structure analysis is a technique that uses the diffraction effect between X-rays and crystals to analyze crystal structures. This process is based on the principle of forward and inverse Fourier transform. Monochromatic X-rays act on a rotating single crystal, and a single crystal diffractometer is used to derive the diffraction intensity data set corresponding to the reciprocal lattice space from the crystal structure corresponding to the forward lattice space by forward transformation. Subsequently, the crystal structure is presented in an analytical or image manner through the calculation of the inverse Fourier number and theoretical processing of the phase.
[0084] The results are as follows Figure 1 As shown, X-ray single crystal structure analysis shows that Figure 1 As shown in part (a), Eu-MOF is a three-dimensional porous lanthanide coordination polymer crystallized in the triclinic space group. The asymmetric unit contains two Eu III ions, two TTDI 4- , two [(CH3)2NH2] + cation, two coordinated H2O molecules and two free H2O molecules. Each Eu III The ion is coordinated with 9 oxygen atoms to form a dodecahedron, of which 8 oxygen atoms come from carboxylic acid and 1 oxygen atom comes from the H2O molecule. Structural studies have shown that Figure 1 As shown in part (b), the nine-coordinated Eu III Ion has a spherical cap square antiprism C 4v The Eu-O bond length range is Adjacent Eu III The ions are connected in an orderly manner through the carboxyl groups of the ligands to form a one-dimensional (1D) chain, and then form a two-dimensional (2D) plane ( Figure 1 Finally, it connects with the ligand to form a three-dimensional framework with a porosity of 47.7% ( Figure 1 (d) in the
[0085] 1-2. Infrared spectrum test:
[0086] like Figure 2 As shown in the infrared spectrum test, the vibration band of Eu-MOF obtained in Example 1 is significantly different from that of H4TTDI, indicating that Eu-MOF and H4TTDI have synergy. Simulation and test X-ray powder diffraction of Eu-MOF ( Figure 3 ) patterns are consistent, indicating that Eu-MOF is a pure phase.
[0087] 1-3. Stability test under different conditions
[0088] like Figure 4 As shown in part (a), the XRD spectra of Eu-MOF immersed in different solvents for 24 hours are consistent with the simulation results, indicating that the compound has high stability in common solvents. In addition, in order to study the stability of Eu-MOF under different acid and base conditions, the XRD spectra of its powder immersed in different acid and base solutions for 24 hours were analyzed. The results are shown in Figure 4 As shown in part (b), it can be seen that the Eu-MOF obtained in Example 1 is stable in the pH range of 2 to 13. Therefore, Eu-MOF has high stability in common solvents and acid-base conditions.
[0089] 2. Thermogravimetric test:
[0090] The Eu-MOF obtained in Example 1 was heated from 25°C to 1200°C at a heating rate of 10°C / min under a nitrogen atmosphere. Figure 5 As shown, it can be seen that the loss of solvent DMF in the first stage is 16.3%, which is very close to the theoretical value of 15.1%. The main framework begins to degrade at around 550°C, indicating that Eu-MOF has good thermal stability.
[0091] 3. Luminescence test
[0092] The Eu-MOF obtained in Example 1 was chemically measured by chemiluminescence. The chemical reaction can produce a product in an electronically excited state. When the product molecule undergoes a radiative transition or transfers energy to other luminescent molecules so that the molecule undergoes a radiative transition again, luminescence occurs.
[0093] In the luminescence test, Eu-MOF showed for the first time a blue-shifted and enhanced fluorescence sensing of UA with a fast response and high sensitivity, with a detection limit of 0.062 μM. Figure 8 In addition, Eu-MOF was made into thin films, LED lamp beads and test papers and their detection effects were tested. The results are shown in Fig. 9 shown.
[0094] 4. Detect the selectivity of Eu-MOF for fluorescence detection of biomarkers.
[0095] Through solid-state fluorescence testing, it was found that the fluorescence emission peaks of H4TTDI and Eu-MOF appeared at λ em =558nm(λ ex =498nm) and λ em =554nm(λ ex =496nm)( Figure 6In part (a), the wavelength range was set, and 0.1 M solutions containing different biomarkers, including uric acid (UA), tartaric acid (TA), malachite green (MG), tri-n-hexyl citrate (THC), caffeic acid (CAA), gallic acid (GA), fatty acid (FA), homovanillic acid (HVA), dopamine (DA), maleic acid (MA), nicotinic acid (NA), ascorbic acid (AOA), geranic acid (GGA) and citric acid (CA), were prepared and added to 1 mg / mL Eu-MOF aqueous suspension in 10 μL aliquots to detect the selectivity of Eu-MOF.
[0096] The experimental results show that the addition of UA significantly enhances the fluorescence emission of Eu-MOF ( Figure 8 Part (a) in the figure), it can also be intuitively confirmed by naked eye recognition ( Figure 8 In addition, uric acid (5×10 -3 M, in Na3PO4 solution), and a fluorescence titration experiment was performed. The fluorescence intensity of the Eu-MOF suspension increased and blue-shifted with the addition of UA solution ( Figure 8 In part (b), in order to better realize the application detection, the same concentration of UA was added to other substances in the simulated urine. The results showed that the emission intensity ratio of the Eu-MOF suspension still increased significantly, indicating that the Eu-MOF fluorescent sensor of uric acid has good anti-interference ability and can realize the detection of simulated urine. Figure 8 As shown in part (d), the fluorescence experiment shows that UA significantly enhances the fluorescence emission of Eu-MOF, and visual identification also confirms this finding. In addition, in order to better realize the application detection, UA was added to the simulated urine to prepare solutions with UA concentrations of (1) 0.1μM, (2) 1μM, (3) 10μM and (4) 100μM. We found that the emission intensity ratio of the Eu-MOF suspension still increased significantly, indicating that Eu-MOF fluorescent sensing of uric acid has good anti-interference ability and can realize the detection of simulated urine, further expanding the application potential of MOF.
[0097] 5. Fluorescence behavior:
[0098] The fluorescence sensing mechanism of MOF is generally: (1) changes in crystal structure or main chain; (2) competitive absorption; (3) energy transfer; (4) strong skeleton-molecule interaction; (5) electron transfer; (6) absorbance enhancement mechanism.
[0099] The test shows that the Eu-MOF obtained in Example 1 of the present invention does not form hydrogen bonds and ligand bonds, and the XRD patterns before and after remain unchanged, thus eliminating the possibility of fluorescence induction due to changes in the crystal structure or backbone structure. Figure 6 The UV-visible absorption spectrum showed that the incorporation of UA caused a significant change in the absorption band due to the interaction, which may be the reason why Eu-MOF has specific selective fluorescence recognition for UA. The subsequent UV titration experiment further verified the results. UA was added to the prepared 3mL Eu-MOF solution, and the absorbance increased with the increase in the molar amount of UA. Therefore, the perception mechanism of Eu-MOF for uric acid involves the absorption enhancement (ACE) mechanism. The solid-state UV-visible spectra of H4TTDI and UA were then measured, and the results are shown in Figure 7 As shown in parts (a)-(c), the energy gap is the thermodynamic driving force for electron transfer between Eu-MOF and the target analyte. Figure 7 As shown in part (d), the lowest unoccupied molecular orbital energy level (LUMO) and the highest occupied molecular orbital energy level (HOMO) of the H4TTDI ligand with UA were calculated by density functional theory (DFT). The analysis found that there is a significant energy difference between the LUMO energy level of the H4TTDI ligand and the LUMO energy level of the UA ligand, which is the thermodynamic driving force for electron transfer between Eu-MOF and the target analyte. Since the LUMO energy level of uric acid is slightly higher than that of the H4TTDI ligand, electrons move more easily from donors to acceptors, triggering fluorescence enhancement. Therefore, the fluorescence sensing effect of UA can be explained by three mechanisms: absorption enhancement, energy transfer, and photoinduced electron transfer (PET).
[0100] 6. Conductivity test
[0101] The proton conductivity of the Eu-MOF obtained in Example 1 was tested, and the results were as follows: Fig.10 The results show that at 98% relative humidity and 55°C, the maximum value of its proton conductivity is 3.34×10 -3 S cm -1 .
[0102] The above exploration of the practical application of Eu-MOF in UA detection shows that the fluorescence decreases with decreasing concentration, which proves that the Eu-MOF obtained in Example 1 has the potential to be used as a fluorescent probe for rapid, direct and real detection of UA.
[0103] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.
Claims
1. A method for preparing a europium-based metal-organic framework for fluorescent detection of uric acid, characterized in that: The following steps are involved: The H4TTDI and Eu(NO3)3·6H2O are mixed and then added to the binary solution, and then lactic acid is added after ultrasonic treatment, and the mixture is stored under heating conditions, and finally subjected to post-treatment to obtain the europium-based metal-organic framework; The ultrasonic treatment time is 30 min, and the ultrasonic power is 360 W; The heating condition is 140°C and the storage time is 3 days; The ratio of the added amounts of H4TTDI, Eu(NO3)3·6H2O, binary solution and lactic acid is 0.05mmol:0.08mmol:7mL:0.2mL; The binary solution is a mixed solution of DMF and water.
2. The method for preparing a europium-based metal-organic framework for fluorescent detection of uric acid according to claim 1, characterized in that: The volume ratio of DMF to water is 5:
2.
3. The method for preparing a europium-based metal-organic framework for fluorescent detection of uric acid according to claim 1, characterized in that: The post-treatment includes cooling, filtering, washing and air drying.
4. A europium-based metal-organic framework for fluorescent detection of uric acid prepared by the preparation method according to any one of claims 1 to 3, characterized in that: The molecular formula is: {[(CH3)2NH2]2[Eu(TTDI)H2O]2·2H2O·7DMF} n 。 5. Use of the europium-based metal-organic framework for fluorescent detection of uric acid as claimed in claim 4 in uric acid fluorescence sensing.
Citation Information
Patent Citations
Double-ligand europium-based metal organic framework material and preparation method and application thereof
CN111808295A
Preparation method of nanoscale dual-wavelength bonding type fluorescent anti-counterfeiting fiber
CN114622297A